Loser Consumer - Satellite TV Soccer Moms Will Hate. - Perry, T.S (IEEE spectrum)
Sirius, first demonstrated, satellite TV for cars at the January 2003 Consumer Electronics Show in Las Vegas. They developed an impressive new transmission technology that breaks up the video signal and combines chunks of it with each of the more than 130 radio channels that fill Sirius's allocated 12.5 megahertz of spectrum. Existing radio receivers screen out that signal as noise, but the new TV receivers recognize the signal as data and decode it. Low-bandwidth satellite-video-subscription services with a small demographic, few channels, and high initial cost seem doomed to failure. On the bright side, adding video to satellite radio will permit measurement of whether losses escalate linearly or are a function of broadcast bandwidth.